Pengaruh Pelatihan Dan Disiplin Kerja Terhadap Kinerja Pegawai Studi Kasus Pada Dinas Pariwisata Dan Kebudayaan Kabupaten Garut (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
This research aims to evaluate the influence of training and work discipline on employee performance at the Garut Regency Tourism and Culture Office. Quantitative methods with descriptive and associative approaches were used in this research. The population involved all Civil Servants as Executives in the Service, with a saturated sample of 35 people. Data was collected through a validated and reliable questionnaire, then analyzed using multiple correlation and F test in the SPSS 28 for Windows program. The research results show that training has a positive and significant effect on employee performance (t = 3.141, p < 0.05). Likewise, work discipline has a positive and significant influence on employee performance (t = 3.420, p < 0.05). Simultaneously, training and work discipline simultaneously have a positive and significant effect on employee performance (fcount = 32.620, p < 0.05). The conclusion of this research shows that investment in training and application of work discipline can positively improve employee performance at the Garut Regency Tourism and Culture Office. These findings provide a basis for developing more effective Human Resources management policies to support the achievement of optimal performance in the context of local government agencies..